Eco-innovation and the edible insect value chain: A systematic review - Jaqueline Geisa Cunha Gomes; Marcelo Tsuguio Okano; Samira Nascimento Antunes; Henry de Castro Lobo dos Santos; Edson Luiz Ursini; Oduvaldo Vendrametto (Contemporary Economics, 2024)
The growing interest in edible insects as a component in animal feed and human food has caught the atten- tion of researchers from various fields, resulting in a multidisciplinary approach. This emerging value chain positions itself as a sustainable and innovative alternative when compared to traditional protein chains. In this scenario, the objective of this article is to conduct a systematic review to investigate and present research on the consumption of insects by humans and their use as animal feed in an eco-innovation context. Our investigations indicate that research on the value chain of edible insects is present on almost all continents, revealing a growing interest, especially in developing countries. In these regions, insect consumption not only addresses issues of food security but also contributes to income generation. The increase in research on alternative protein sources, such as edible insects, seems to align with a broader trend toward sustainability in food production, underscoring the relevance of the topic in the search for environmentally friendly solutions. Noteworthy results include global recognition and collaborative efforts in edible insect research, highlighting a collective approach to addressing challenges and exploring opportunities. This global cooperation under- scores the significance of the topic and the necessity for innovative solutions in addressing environmental and food security challenges.
Keywords: Q0; 330; eco-innovation; edible insects; sustainability; human food; animal feed